Hypsochromic Shift of Multiple‐Resonance‐Induced Thermally Activated Delayed Fluorescence by Oxygen Atom Incorporation - Tanaka, Hiroyuki; Oda, Susumu; Ricci, Gaetano; Gotoh, Hajime; Tabata, Keita; Kawasumi, Ryosuke; Beljonne, David; Olivier, Yoann; Hatakeyama, Takuji (Angewandte Chemie International Edition, 2021)
Herein, we reported an ultrapure blue multiple‐resonance‐induced thermally activated delayed fluorescence (MR‐TADF) material (ν‐DABNA‐O‐Me) with a high photoluminescence quantum yield and a large rate constant for reverse intersystem crossing. Because of restricted π‐conjugation of the HOMO rather than the LUMO induced by oxygen atom incorporation, ν‐DABNA‐O‐Me shows a hypsochromic shift compared to the parent MR‐TADF material (ν‐DABNA). An organic light‐emitting diode based on this material exhibits an emission at 465 nm, with a small full‐width at half‐maximum of 23 nm and Commission Internationale de l'Eclairage coordinates of (0.13, 0.10), and a high maximum external quantum efficiency of 29.5 %. Moreover, ν‐DABNA‐O‐Me facilitates a drastically improved efficiency roll‐off and a device lifetime compared to ν‐DABNA, which demonstrates significant potential of the oxygen atom incorporation strategy. A multiple‐resonance‐induced thermally activated delayed fluorescence material that comprised oxygen, nitrogen, and boron atoms (ν‐DABNA‐O‐Me) was synthesized via one‐shot double borylation. An OLED device employing the fabricated ν‐DABNA‐O‐Me exhibits deep‐blue electroluminescence with a small full‐width at half‐maximum and a high external quantum efficiency with minimum efficiency roll‐off.